Zer - oo4 Musculoskeletal disorders and perception of working conditions: a survey of brazilian dentists in São Paulo - Garbin, Artenio Jose Isper; Soares, Gabriella Barreto; Arcieri, Renato Moreira; Garbin, Cléa Adas Saliba; Siqueira, Carlos Eduardo (ARCHIVES OF HEALTH INVESTIGATION, 2016)
The aim of this study is to evaluate the musculoskeletal disorders, and the workers’ perception about job-factors, and also to identify the relationship between the intensity of pain and disability in dentists with musculoskeletal disorders. Cross sectional and correlational research was conducted with 204 dentists who work in a Public Health Service in Brazil. Data were collected through interviews, using the Nordic Questionnaire, and Work-related activities that may contribute to job-related pain. The Pain Disability Questionnaire (PQD) and the Numeric pain scale were also applied to workers with pain. Results showed that most dentists (81.4%) had musculoskeletal disorders, especially in neck, shoulders and lower back. It was found that the presence of symptoms in the neck (15.7%), shoulders (12.7%) and lower back (15.7%) were the major causes of absence from work over the past 12 months. The job factors perceived as most problematic were: bending or twisting your back in an awkward way, continuing to work when injured or hurt and working in the same position for long periods. The comparison between symptomatic and asymptomatic dentists showed significant difference (p<0.05) in their perception of job-factors. The analysis of the intensity of pain and the disability, with PDQ, in symptomatic dentists showed an average pain intensity of 3.8 and mean scores of the PDQ total (11.46) pointing to moderate disability in this group of workers. There was a significant correlation of strong magnitude (r = 0.697) between pain intensity and the total score of disability caused by pain. Conclusion: The analysis of the occurrence of pain and work related problems show that the MSD are already interfering significantly in the dentists’ lives. And had a significant correlation between pain intensity and the disability caused by pain in dentists. Descriptors: Occupational Diseases; Musculoskeletal Pain; Dentists. Acknowledgment: FAPESP #2012/10187-8